Feasibility of sentinel lymph node mapping in ovarian tumors: A systematic review and meta-analysis of the literature - Ataei Nakhaei, Saeideh; Mostafavi, Sayyed Mostafa; Farazestanian, Marjaneh; Hassanzadeh, Malihe; Sadeghi, Ramin (Frontiers in Medicine, 2022)
Purpose of the report: Since the presence of lymph node metastases upstages the disease and in order to reduce the morbidity of total lymphadenectomy, sentinel lymph node (SLN) mapping in ovarian mass has been the focus of extensive research. The present study aims to review all the literature associated with ovarian SLN mapping and assess the feasibility of ovarian SLN mapping. Materials and methods: PubMed and Scopus were searched using the following keywords: (Sentinel lymph node) AND (Ovary OR Ovarian) AND (Tumor OR Neoplasm OR Cancer). All studies with information regarding sentinel node biopsy in ovaries were included. Different information including mapping material, injection sites, etc. were extracted from each study. Two indices were calculated for included studies: detection rate and false negative rate. Meta-analysis was conducted using Meta-MUMS software. Pooled detection rate, sensitivity, heterogeneity and publication bias were evaluated. Quality of the studies were evaluated using the Oxford center for evidence-based medicine checklist. Result: Overall, the systematic review included 14 studies. Ovarian SLN detection rate can vary depending on the type of tracer, site of injection, etc., which signifies an overall pooled detection rate of 86% [95% CI: 75-93]. The forest plot of detection rate pooling is provided (Cochrane Q-value=31.57, p=0.003; I2=58.8%). Trim and fill method resulted in trimming of 7 studies, which decreased the pooled detection rate to 79.1% [95% CI: 67.1-87.5]. Overall, pooled sensitivity was 91% [59-100] (Cochrane Q-value=3.93; p=0.41; I2=0%). However, a few studies had enough data to calculate the sensitivity of sentinel node mapping in lymphatic staging of ovarian malignancies. Conclusion: SLN mapping in ovarian tumors is feasible and seems to have high sensitivity for detection of lymph node involvement in ovarian malignant tumors. Mapping material, injection site and previous ovarian surgery were associated with successful mapping. Larger studies are needed to better evaluate the sensitivity of this procedure in ovarian malignancies.